1987
DOI: 10.1007/bf00253966
|View full text |Cite
|
Sign up to set email alerts
|

High-dose methotrexate therapy with leucovorin rescue: in vitro investigations on human osteosarcoma cell lines

Abstract: High-dose methotrexate (MTX) therapy with subsequent leucovorin (LV) rescue (HDMTX-LV) in the treatment of osteosarcoma is based on the assumption that this tumor has a deficient uptake system for MTX and reduced folates. To simulate features of HDMTX-LV therapy protocols in vitro, sensitive and MTX-resistant human osteosarcoma cell lines and a lymphoblastoid cell line were exposed to MTX and/or LV at various dosages and time schedules and the effects on DNA metabolism and on cell growth were evaluated. The da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Among the clinically relevant conclusions which can be drawn from the present study, the optimum time interval between MTX and FA appears to be around 18-24 h; a marked reduction in MTX cytotoxicity occurs during shorter intervals. This observation concurs well with the similar conclusions of a comparable study on human osteosarcoma cell lines (Diddens et al, 1987) and with the data reported by Sirotnak et al (1978) (Stoller et al, 1979). This finding may explain why patients treated by standard dose MTX plus FA rescue, exhibited a significantly lower response rate than those receiving only MTX, in a randomised placebo-controlled study (Browman et al, 1990).…”
Section: Discussionsupporting
confidence: 94%
“…Among the clinically relevant conclusions which can be drawn from the present study, the optimum time interval between MTX and FA appears to be around 18-24 h; a marked reduction in MTX cytotoxicity occurs during shorter intervals. This observation concurs well with the similar conclusions of a comparable study on human osteosarcoma cell lines (Diddens et al, 1987) and with the data reported by Sirotnak et al (1978) (Stoller et al, 1979). This finding may explain why patients treated by standard dose MTX plus FA rescue, exhibited a significantly lower response rate than those receiving only MTX, in a randomised placebo-controlled study (Browman et al, 1990).…”
Section: Discussionsupporting
confidence: 94%
“…Standard doses (0.5 gm-2) and high doses (2.5 gm-2) of MTX generate median MTX CSF values of 8 x 10-8 M and 6 x I0 -7 M respectively (Thyss et al, 1987). Diddens et al (1987) established in a lymphoblastoid cell line that the cytotoxic effect of high concentrations of MTX was reversed by relatively low concentrations of simultaneously added leucovorin. There is thus a potential risk of competition between folates and antifolates in CSF during standard or even high dose MTX plus FA rescue in the treatment of childhood ALL.…”
Section: Resultsmentioning
confidence: 99%
“…Clarke et al 27 demonstrated that folinic acid (leucovorin TM /folate) administered in drinking water prevented the development of MTX-induced mucositis entirely. It has been shown in humans that folate (leucovorin) administered intravenously has the potential to reinitiate tumor cell survival if given within 24 h. 34,35 Sepehr et al (2003), reported that cecal bacteria-synthesized folate was not absorbed or stored in substantial amounts in the liver, indicating that systemic folate distribution is limited. The mechanism of protection by TH-4 in non-tumor bearing animals may have been the result of delivering a micro dose of folate to the site of damage, suggesting that a dose of 10 9 cfu/mL was insufficient DAR ( Table 4; p < 0.001) for "Net" small intestinal sucrase activity (average).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%